Evaluation of p16INK4a immunostaining for the detection of high-grade changes in cervical cytology - Tabrizi, Sepehr N.; Tan, Sarah E.; Knebel Doeberitz, Christina von; Tan, Jeffery; Quinn, Michael A.; Garland, Suzanne M. (Pathology, 2015)
Since its introduction in Australia in 2007, the human papillo-mavirus (HPV) vaccine has led to a markedly lower prevalence of vaccine targeted HPV genotype infections as well as HPV disease including genital warts and histologically confirmed high-grade (HG) cervical abnormalities. To increase the ability to identify abnormal cells in lower prevalence, adjunct markers can be incorporated to improve the sensitivity and specificity of cytology test. One such marker is p16INK4a(p16), which is detectable in cells expressing the E7 oncogene encoded by high-risk HPVs (HR-HPV). In this study, the sensitivity and specificity of p16 immunostaining in detection of underlying HG lesions was evaluated in a cohort of 454 women undergoing surgical treatment for biopsy proven cervical dysplasia. Overall, p16 positive cells were detected in 321 (71%) of cytology preparations evaluated. Comparison of p16 staining on cytological preprations to histology diagnosis available on 212 patients, showed 26 (54%), 41 (78%) and 80 (90%) of cytology preparations to be p16 positive in women with CIN1, CIN2 and CIN3, respectively (p<0.005). HPV16 and 18 were the most prevalent genotypes in HG lesions and were highly correlated with p16 staining. p16 staining provides an additional marker which can assist in better detecting underlying HG lesion in cytology smears with low disease prevalence.
Online 19 February 2016
Im Text ist INK4a hochgestellt
Gesehen am 25.06.2020